2011
DOI: 10.1002/jmv.22235
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of echovirus 30 involved in aseptic meningitis cases in Brazil (1998–2008)

Abstract: Aseptic meningitis is one of the most common neurological disorders caused by enteroviruses. Among them, Echovirus 30 (E30) is described as the main etiological agent of many outbreaks and sporadic cases. This study investigated the genomic variability of E30 isolated from the cerebrospinal fluid (CSF) of aseptic meningitis cases that occurred from 1998 to 2008 in Brazil. Over a 10-year period (1998-2008), 302 non-polio enteroviruses were isolated, of which 177 were identified as E30 (58.6%). Phylogenetic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Their seasonal distribution followed the recognized pattern of peaks during summer with a reducing number of cases in subsequent months [Yamashita et al, ]. Members of HEV‐B have been widely described as the most common cause of aseptic meningitis cases and outbreaks worldwide [Bailly et al, ; Mirand et al, ; dos Santos et al, ]. However, this study also found a scattering of rarer types, often in single years.…”
Section: Discussionmentioning
confidence: 53%
“…Their seasonal distribution followed the recognized pattern of peaks during summer with a reducing number of cases in subsequent months [Yamashita et al, ]. Members of HEV‐B have been widely described as the most common cause of aseptic meningitis cases and outbreaks worldwide [Bailly et al, ; Mirand et al, ; dos Santos et al, ]. However, this study also found a scattering of rarer types, often in single years.…”
Section: Discussionmentioning
confidence: 53%
“…3) (Zhao et al 2005; dos Santos et al 2011). All Chinese strains belonged to group C, which further formed two distinct clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous aseptic meningitis outbreaks that are caused by different lineages of ECHO30 have been reported during the last decade in many countries (15,21,32). In Guangdong Province, China, ECHO30 was first isolated from a sewage sample in 2010 through environmental surveillance; subsequently, this virus was continually but not frequently detected in sewage of Guangzhou City (7).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, repeated outbreaks and nationwide epidemics of ECHO30 have occurred in Europe (8)(9)(10)(11), Asia (12)(13)(14), and America (15)(16)(17). In China, high frequencies of ECHO30 detection in meningitis cases have been documented in the last few years in different coastal provinces, including Zhejiang (18), Jiangsu (14), and Shandong (19,20).…”
mentioning
confidence: 99%